Keterlibatan Dan Berkesinambungan Lembaga Masyarakat Desa Hutan Dalam Pengelolaan Dan Pemanfaatan Lahan Perhutani Untuk Pembangunan Desa - Nanda Nugraha (PAPSEL RESEARCH AND CONSULTANT, 2024)
This research is motivated by the lack of regulations on forest area lending, the incompatibility between the implementation and cooperation agreements and the lack of awareness of forest village communities in maintaining forests. The formulation of the problem in this study is: How is the participation of Forest Village Community Institutions in the use of forestry land in Langkaplancar Village, Langkaplancar District, Pangandaran Regency? The research method used by the researcher is qualitative research. The informants in this study were 5 people. The data collection techniques in this study are observation, interviews and documentation. The analysis steps carried out are data reduction, data display and data verification. The results of the study show that the participation of forest village communities in Perhutani's land use in Langkaplancar Village, Langkaplancar District, Pangandaran Regency has not been optimal. This is shown from 4 dimensions as a measuring tool, 2 dimensions are optimal and 2 dimensions are not optimal. The dimensions of participation in decision-making are the lack of optimal indicators of planning deliberation, the indicators of planning preparation and the lack of optimization of indicators of planning approval. The dimension of participation in implementation is optimal. The dimension of participation in taking benefits has been optimal and the dimension of participation in evaluation has not been optimal, such as in examining finances has not been optimal and the monitoring carried out on activities carried out by the Forest Village Community Institution has not been optimal.